La pudricion negra de las raices del cafeto en la region del Escambray - Herrera Isla, L.=700 1 Grillo Ravelo, H.
(En, Es)
ilus., 9 ref.
Keywords: COFFEA; PUDRICIONES; RAICES; ROSELLINIA; EPIDEMIOLOGIA; METODOS; CUBA